2021
DOI: 10.1016/j.nima.2021.165598
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of cumulative photofission yields of 235U and 238U with a 16 MeV Bremsstrahlung photon beam

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…In the frame of a long-term research program conducted by the Nuclear Measurement Laboratory of CEA IRESNE Institute in France, this work follows the study recently reported in [19], which provided cumulative photofission yields of 235 U and 238 U with a 15.8 MeV Bremsstrahlung beam produced by a linear electron accelerator (LINAC) in CINPHONIE casemate of CHICADE nuclear facility [20]. We present here new cumulative photofission yields for 239 Pu, and again for 235 U and 238 U, which are measured with the same setup but with an endpoint electron energy of 17.5 MeV.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In the frame of a long-term research program conducted by the Nuclear Measurement Laboratory of CEA IRESNE Institute in France, this work follows the study recently reported in [19], which provided cumulative photofission yields of 235 U and 238 U with a 15.8 MeV Bremsstrahlung beam produced by a linear electron accelerator (LINAC) in CINPHONIE casemate of CHICADE nuclear facility [20]. We present here new cumulative photofission yields for 239 Pu, and again for 235 U and 238 U, which are measured with the same setup but with an endpoint electron energy of 17.5 MeV.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Another important task for the characterization of nuclear materials by active photon interrogation is the accurate measurement of the cumulative yields of photofission products, as reported in [10] for 235 U and 238 U. Additional experiments have been recently performed to measure the cumulative photofission yields of 239 Pu, which will be published soon, as such data are extremely rare so far in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…A series of photofission products liable to allow 235 U vs. 238 U discrimination in the global photofission signal have been identified in [10] . This work will be continued for uranium vs. plutonium differentiation using our measured uranium and plutonium photofission yields.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations